Ionizing radiations in the hemodinamic service: the nursing perception - Gomes, Marcia de Deus; da Silva, Lolita Dopico (Online Brazilian Journal of Nursing, 2006)
One is about a research developed in the Course of Magister of the College of Nursing the UERJ. The object of the research is the perception of the workers of nursing who act in the service of hemodinâmica concerning the ionizing radiation. The general objective was to analyze the perception of the worker of nursing, that acts in the hemodinâmica service, concerning the conviviality with the risk proceeding from the ionizing radiation. The used theoretical was the Model of Beliefs in health of Rosenstok (1974). How much to the methodology case study is about a descriptive study in the modality, with boarding in the treatment of the data qualitative. The population was composed of the workers of nursing of the Service of Hemodinâmica. The technique of the half-structuralized interview was used. The results had been grouped in accordance with the methodology of the analysis of content of Bardin. Two categories had been created that are being analyzed, one on the perception of susceptibility and the consequences to the risk and another category on the protection perception and barriers to the protection